Observer-based output feedback control design for a fractional ODE and a fractional PDE cascaded system. (September 2022) - Amiri, Shadi; Keyanpour, Mohammad; Masoudi, Mohsen
Abstract: This paper considers a new bi-directional cascaded system of a fractional ordinary differential equation (FODE) and a fractional partial differential equation (FPDE) which interacts at an intermediate point. The space-dependent coefficients, interaction between the FODE and FPDE at an intermediate point and the presence of fractional calculus makes the FODE–FPDE cascaded system, representative. In this note, we first apply an invertible integral transformation to convert the system into a FODE–FPDE coupled system, as the target system, which is Mittag–Leffler stable. Using the backstepping method and under some assumptions of the space-dependent coefficients, we work out the kernel functions in the transformation and we design a boundary controller. Also, by the invertibility of the transformation, we show the Mittag–Leffler stability of the closed-loop system via the Lyapunov approach. Second, we propose an observer for which we prove that it can well estimate the original cascaded system. Then, we design an output feedback boundary control law and show that the closed-loop system is Mittag–Leffler stable under the designed output feedback control law. Finally, we present some numerical illustrations to show the correctness of the theoretical results. Highlights: A new FODE–FPDE coupled system interacting at an intermediate point is considered. Using backstepping method, observer and observer-based output feedback are presented. The state and the output feedback controllers for the coupled system are designed. The Mittag–Leffler stability of the closed-loop system is proved.